(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The role of information disclosure as a moderator in driving the effect of sustainability reporting on profitability was investigated. The study population entailed 25 listed companies on the Iraq Stock Exchange over the period of 2014-2017. The companies were assessed to determine their level of sustainability disclosure as reported in their annual reports. In realizing the research objectives, this study derived secondary data from the companies’ annual report which was then analyzed using several panel data regression techniques specifically the fixed effect estimation, the random effects estimation and the ordinary least square regression. Using the Triple Bottom Line (TBL) entailing the dimensions of economy, social and environment, a total of 167 disclosure indices were investigated utilizing a zero-one procedure. Each company’s corporate social responsibility disclosure was extracted and rated to determine its disclosure level. The relationships between the study variables were determined by examining the companies’ sustainability reporting disclosures of the independent variables and the performance metrics using the dependent variable of accounting data (ROA). The findings reveal that the companies’ corporate social responsibility disclosure is significantly correlated to their financial performance according to the accounting data. Implications-wise, the findings can enhance the confidence of investors to invest in companies with solid corporate governance. The findings of this study enrich the existing body of knowledge and drive the adoption of transparency among policymakers.